ANALISIS HASIL BELAJAR SISWA SMK JURUSAN JASA BOGA TERHADAP MINAT BEKERJA SISWA PADA INDUSTRI HOSPITALITY DAN PARIWISATA DI JAKARTA - Yudhiet Fajar Dewantara (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2020)
The purpose of this study was to determine whether there is an effect of student learning outcomes in the Department of Catering on Interest in Working in Hospitality and Tourism which includes cognitive, affective and psychomotor abilities in subjects related to Normative, Adaptive and Productive. Results and Discussion From the results of simple regression analysis there is a positive relationship between learning outcomes and interest in working, the higher learning outcomes, the more interest in work. Hypothesis Test Results Normative dimension with t count > t table (9,174 > 1,98422) and significance value < 0.05 (0.00 < 0.05), so Ho is rejected and Ha is accepted. Hypothesis Test Results